Strategi Pengembangan Bisnis UMKM Dengan Metode Business Model Canvas (Studi Kasus Pada PT. Schon Craft Indonesia) - Niken Maulia Putri; Dewi Nurbaiti (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.Micro, small, and medium enterprises (MSMEs) play an important role in job creation and economic growth in Indonesia. However, in reality, they still face various obstacles. PT Schon Craft Indonesia is an MSMEengaged in the knitting craft industry, with its main products being knitted bags and shoes. The challengesfaced by this SME include branding, marketing, availability of raw materials, relatively slow production,difficulty in ensuring product quality, unspecified market segmentation, and insufficient utilization of socialmedia. Therefore, a strategy is needed, one of which is the Business Model Canvas (BMC). The BMC wasintroduced by Osterwalder & Pigneur (2010) and consists of nine main elements covering all aspects of thebusiness, from customer segmentation to cost structure. This study aims to analyze the implementation ofthe MSME business development strategy of PT Schon Craft Indonesia using the Business Model Canvasmethod, as well as to identify challenges and solutions in its implementation. This study employs a descriptivequalitative approach with data collection techniques through interviews and observations. Data analysistechniques include data reduction, data presentation, and conclusion drawing. The results of the studyindicate that PT Schon Craft Indonesia has fulfilled nine BMC elements, such as the value propositionelement through product quality and innovation, channels through offline and online marketing, and customerrelationships by always prioritizing the best service. However, improvements are needed in the elements ofchannels, value propositions, key resources, key partnerships, and customer segments. Keywords: MSMEs, Strategy, Business Model Canvas